The worst gymnast - Kalkipsakis, Thalia; Oswald, Ash (New York : Feiwel and Friends, 2007)
Gemma accidently kicks her gymnastics coach while trying to do a disastrous vault, and even though she apologized, she begins to think she is being punished when he assigns her extra strength work.
School Library Journal
School Library Journal, January 2008
2.2
3-6.
3-6
Keywords: Girls -- Juvenile fiction; Gymnastics -- Juvenile fiction; Girls -- Fiction; Gymnastics -- Fiction; Schools -- Fiction; Girls -- Fiction; Gymnastics -- Fiction; School stories